INTRAVASCULAR ULTRASOUND SUBTYPES OF UNIFOCAL RENAL ARTERY FIBROMUSCULAR DYSPLASIA. (June 2022) - Xu, Jianzhong; Wu, Qihong; Kang, Yuanyuan; Hong, Mona; Gao, Pingjin; Wang, Jiguang
Abstract : Objective: A binary angiographic classification of renal artery FMD lesions into multifocal or unifocal is well established. The multifocal type, with the 'string-of-beads' appearance, is related to medial FMD. While the unifocal type (focal or tubular type), is not clearly related to specific histological lesions. IVUS is a useful tool, in addition to the angiography for evaluation of the anatomical changes of structures of the vessel wall. The purpose of this study was to reveal the different subtypes of unifocal renal artery fibromuscular dysplasia (FMD) based on intravascular ultrasound (IVUS) and assess the clinical characteristics. Design and method: Thirty-six hypertensive patients (mean age 24 ± 7 years, 13–39 years) with computer tomography angiography (CTA) scan suggestive of unifocal renal artery FMD underwent renal angiography, IVUS and angioplasty, with both immediate and long-term blood pressure (BP) response assessment. Results: Of the total 36 patients, renal angiography revealed focal type in 22 (66.1%) and tubular stenoses in 14 (38.9%) patients. On IVUS, two subtypes of unifocal renal artery FMD were identified include intima-media thickening (IMT, n = 21, 58.3%) and negative remodeling of the whole vessel (NR, n = 15, 41.7%). In the 22 patients with focal type on angiography, 18 (81.8%) showed IMT and 4 (18.2%) showed NR on IVUS. 14 patients with tubular type on angiography, IVUS showed IMT in 3 (21.4%) and NR in 11 (78.6%) patients. No difference in age of onset, gender, BMI, initial BP levels were found between two IVUS subtypes. However, the proportion of BP returning to normal in the immediate term (48 hours after angioplasty procedure) (76.2% vs 26.7%, p = 0.004) and the long-term (1–5years) cure rate of hypertension (90.5% vs 20.0%, p < 0.001) were much higher in the IMT subtype than those in the NR subtype. Conclusions: In this study, we describe a new classification into IMT or NR of unifocal renal artery FMD based on IVUS. Patients with IMT renal FMD were more likely to achieve cure of hypertension.